Design of An Intelligent Tutoring System – Student Model: Predicting Learning Style - Hawari, Nubli; Oktavia, Tanty (Engineering, MAthematics and Computer Science Journal (EMACS), 2024)
Education is very important for everyone, not only for acquiring knowledge but also for improving quality of life and well-being. An Intelligent Tutoring System (ITS) is a computer system that can provide personalized and adaptive learning assistance and support to students. This system is designed to offer effective guidance to students based on their individual abilities and learning styles. ITS utilizes artificial intelligence (AI) technology to understand students' abilities and provide guidance tailored to their needs. Recently, there have been methods to predict learning styles, such as through questionnaires on the EducationPlanner website, but these determinations are often too general. This study aimed to predict the learning styles used by specific students for specific subjects. Researchers conducted this study at XYZ University to determine the learning styles of certain students or groups. With this information, instructional materials and methods can be uniquely designed to cater to the needs of these groups. Based on the evaluation results, the study found that the Logistic Regression model was the best, with a precision of 0.5653 and a hamming loss value of 0.3468. This research demonstrates that information from six selected subjects (English, Religion, Civics, Arts, Physics, and Geography) can be used to determine students' learning styles.